Issues in Indian Public Policies (India Studies in Business and Economics,, 2018)
This book discusses economic development in general and selected public policy issues with a focus on philosophy, Gandhian thoughts and sectoral issues in the Indian context. It presents scholarly contributions on growth and development in India, with particular emphasis on human development in connection with the economy of India and selected developing countries. It brings to the forefront a body of knowledge on philosophy and ethical issues within the domain of public policies relating to development in today's world. The book includes contributions from leading economists and covering a range of issues such as the Indian government's current 'Make in India' drive, the role of the World Bank, managing educational finances, development and higher education policy, inflation, decentralization, inequality, regional development, and linkages between health, nutrition and education. Accordingly, the book not only offers a useful resource for academics, economists and development practitioners, but also has important implications for public policymaking.